ANALISIS PENGAMBILAN DAN PREPARASI SAMPEL BERDASARKAN HASIL PENGUJIAN KADAR NIKEL PADA PT. HALTIM MINING KABUPATEN HALMAHERA TIMUR PROVINSI MALUKU UTARA - Jimmy E. A. Fatubun Fatubun; Yulius G. Pangkung (Jurusan Teknik Pertambangan Program Studi S1 Teknik Pertambangan Fakultas Teknik Pertambangan dan Perminyakan Universitas Papua, 2018)
PT. Haltim Mining is one of the nickel mining companies with sediment resources consist of several layers, namely cover soil, limonite, saprolite and bedrock. About 1.8% of the nickel concentrate would be marketed by the company, but the nickel content sampled for testing by XRF Epsilon 3 tool changes the level between the samples in the Pit and the sample on the stockpile. The results showed that the average level of nickel concentrate sampled at Pit was 1.80%, while the average level of nickel concentrate sampled on Stockpile was 1.75%, with an average difference of 0.09%. Changes in levels were influenced by sampling method, sample preparation and the accuracy of a sampler.